2017
DOI: 10.1111/pim.12492
|View full text |Cite
|
Sign up to set email alerts
|

PEGylation of cationic liposomes encapsulating soluble Leishmania antigens reduces the adjuvant efficacy of liposomes in murine model

Abstract: Although there have been several attempts to develop a vaccine against leishmaniasis, no vaccine in human has been developed yet. Liposomes consisting of 1, 2-dioleoyl-3-trimethylammonium-propane (DOTAP) encapsulating soluble Leishmania antigens (SLA) enhance protective immunity of SLA against Leishmania major infection in mice. However, they immobilized at the injection site because of their positive charge. To overcome the problem, shielding the surface charge with polyethylene glycol (PEGylation) was chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…For the case of cationic liposomes where the depot effect is involved in their immunostimulatory mechanism, pegylation may not be beneficial, depending on the PEG density and length used, as higher PEG concentrations can lead to adverse effects. Work by Kaur and others demonstrated that pegylation of DDA:TDB cationic liposomes resulted in masking of the cationic charge and subsequently reduction of antigen adsorption on the liposome surface. More importantly, high levels of PEG (25%) led to the faster drainage of liposomes from the injection site, thus blocking the depot effect and reducing the Th1-driven immune response. , Similar conclusions were reached by Roces et al, who investigated the effect of biotin–avidin complex on the retention of DDA:TDB liposomes in the lymphatics and the induced immune responses.…”
Section: Combinatorial Adjuvant Strategiesmentioning
confidence: 99%
“…For the case of cationic liposomes where the depot effect is involved in their immunostimulatory mechanism, pegylation may not be beneficial, depending on the PEG density and length used, as higher PEG concentrations can lead to adverse effects. Work by Kaur and others demonstrated that pegylation of DDA:TDB cationic liposomes resulted in masking of the cationic charge and subsequently reduction of antigen adsorption on the liposome surface. More importantly, high levels of PEG (25%) led to the faster drainage of liposomes from the injection site, thus blocking the depot effect and reducing the Th1-driven immune response. , Similar conclusions were reached by Roces et al, who investigated the effect of biotin–avidin complex on the retention of DDA:TDB liposomes in the lymphatics and the induced immune responses.…”
Section: Combinatorial Adjuvant Strategiesmentioning
confidence: 99%
“…When L. major soluble antigen (SLA) or recombinant LACK (rLACK) antigen were delivered subcutaneously together with cholera vaccine to BALB/c mice, a Th1 type response was observed with increased IFN-γ production; however, an exacerbation of infection occurred following challenge with L. major [271]. Liposomes consisting of 1,2-Dioleoyl-3-trimethylammonium-propane (DOTAP) encapsulating SLA with polyethelene glycol (PEG) failed to confer protection in the murine model of Leishmania infection [272]. However, immunostimulatory cationic lipids formed from DOTAP, 1,2-dioleoylsn Glycero-3-phosphoethanolamine (DOPE), and cholesterol encapsulating single-gene expression plasmid of pcLACK showed protection against CL [273].…”
Section: Leishmania Homolog For Receptors Of Activated C Kinase (Lack)mentioning
confidence: 99%
“…The conjugated PEG-hexadecane has a stimulatory adjuvant activity to potentiate a robust humoral and cellular immunity 7. Incorporation of a small amount of PEG into DOTAP liposomes not only increased the passive lymph nodes targeting of liposomes, but also improved the efficiency of the vaccines 8. PEGylation of lipopeptide R 4 Pam 2 Cys facilitated antigen uptake and presentation to T cells and showed improved antigen-specific CD8 + T-cell response 9.…”
Section: Introductionmentioning
confidence: 99%